Pembinaan UMKM Melalui Inovasi Produk Pemanfaatan Belimbing Wuluh Menjadi Masker Organik - Muhlis Ade Putra; Nurlita Apriyanti; Febi Febriyanti; Irma Suciati; Nurfitriah Ningsih; Magfiratus Sholeha; M.fitrah Anjani; Irma Mardian (Cakrawala: Jurnal Pengabdian Masyarakat Global, 2024)
Product innovation is one way for UMKM to win the competition. Skin care is the most sought after product lately. Therefore, the innovation of skin care facial masks from starfruit is the choice of the fostered UMKM. This UMKM development was carried out in South Rabangodu Subdistrict in the UMKM group. The implementation method is by introducing innovation, producing face masks using abundant local materials in locations, then marketing them through online social media and offline sales. The innovation of using starfruit to make organic facial masks is quite popular with the public. Promotion via online and offline social media supports accelerated product development and adoption. The innovation of the starfruit mask has become a new business option for UMKM in the South Rabangodu Region